Synthesis and Study of the Antimicrobial Activity of Modified Polyvinyl Alcohol Films Incorporated with Silver Nanoparticles (Baghdad Science Journal, 2023)
A new class of biologically active nanocomposites and modified polymers based on poly (vinyl alcohol) (PVA) with some organic compounds [II, IV, V and VI] were synthesized using silver nanoparticles (Ag-NPs). All compounds were synthesized using nucleophilic substitution interactions and characterized by FTIR, DSC and TGA. The biological activity of the modified polymers was evaluated against: gram (+) (staphylococcus aureus) and gram (-): (Es cherichia coli bacteria). Antimicrobial films are developed based on modified poly (vinyl alcohol) MPVA and Ag-NPs nanoparticles. The nanocomposites and modified polymers showed better antibacterial activities against Escherichia coli (Gram negative) than against Staphylococcus aureus (Gram positive). This work also studied the effect of using different amounts of nanoparticles on the effectiveness against bacteria and it was found that nanocomposite (P2/Ag 5%) has superior antibacterial properties against Escherichia coli.